Review of Grace Davie's Analytical Work in the Handbook of the Sociology of Religion and Its Relevance to the Indonesian Context - Roberto Arieza Martin Purba; Mohammad Taufiq Rahman; Yeni Huriyani (Jurnal Multidisiplin Sahombu, 2026)
The contribution of Davie in "Evolving Sociology of Religion: Themes and Variations" provides an understanding on how religion, historically geocentric, develops. The above is meant to provide understanding on the state of Islam in Indonesia. The study intends to explain the evolution of the sociology of religion from Marx to Weber and Durkheim until a contemporary paradigm, and how these are relevant to the context of Indonesia. Davie’s analytical framework, which emphasizes the geographical and historical contingencies in understanding religious phenomena, offers a critical perspective for analyzing the complex dynamics of religion in Indonesia. The development of religion in Indonesia challenges the simplistic dichotomy between European secularization theory and American rational choice theory. Indonesia thus serves as an example of the need for alternative approaches that are sensitive to local contexts, giving rise to the concept of “glocalization.”